2020
DOI: 10.21203/rs.3.rs-15436/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Potential Crucial Genes in Atrial Fibrillation: A Bioinformatic Analysis

Abstract: Abstract Background Atrial fibrillation (AF) is at least partially heritable, affecting 2-3% of the population in Europe and the USA. However, a substantial proportion of heritability is still lacking. In the present study, we aim to identify potential crucial genes associated with AF through bioinformatic analyses of public datasets. Methods Microarray data sets of GSE115574, GSE31821, GSE79768, GSE41177 and GSE14975 from the Gene Expression Omnibus (GEO) database were… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…To gain evidence for reductome-signature in TG hearts, gene ontology pathway analysis was carried out by panther and string analysis (26,27). Panther analysis classify the proteins on the basis of biological function and pathways (28).…”
Section: Discussionmentioning
confidence: 99%
“…To gain evidence for reductome-signature in TG hearts, gene ontology pathway analysis was carried out by panther and string analysis (26,27). Panther analysis classify the proteins on the basis of biological function and pathways (28).…”
Section: Discussionmentioning
confidence: 99%
“…These pathways can also be used to target genes that might be involved in pathogenesis of atrial fibrillation and can be used as therapeutic targets and potential biomarkers. Biomarkers for atrial fibrillation are already being identified [ 129 , 130 ] and could be useful in clinical risk assessment and outcomes for individuals with atrial fibrillation.…”
Section: Conclusion Challenges and Future Directionsmentioning
confidence: 99%